SISTEM INFORMASI PENGELOLAAN BARANG PERSEDIAAN MILIK NEGARA DI PUSAT PENILAIAN PENDIDIKAN - Erwin Suhandono; Arif Hidayat (Fakultas Teknik Universitas Pancasila, 2020)
The Educational Assessment Center is a Government Agency under the Ministry of Education and Culture's Research and Development Agency. To carry out office activities, it is necessary to be supported by the availability of supplies to support these activities. Therefore, it is necessary to improve the management of state owned goods. Where the data processing is still done manually, that is, the demand for goods is done by filling out the paper form, so that the process of processing requires more time. Based on these problems an information system is needed. This information system is designed based on Object Oriented by using the Unified Modeling Language (UML) as a system modeling language to facilitate employees in processing data of State owned goods..